Bacteria of Phlebotominae Sand Flies Collected in Western Iran - Somayeh Rafatbakhsh-Iran; Aref Salehzadeh; Rasoul Yousefimashouf; Mohammad Najafimosleh; Zahra Karimitabar; Maryam Khedri (Iranian Journal of Health, Safety and Environment, 2015)
Microorganisms particularly bacteria presenting in insects such as Phlebotominae may play an important role in the epidemiology of human infectious disease. Nowadays, because of vector implications, the routine methods of controlling and spraying have no more beneficial effects on vectors and reservoirs. Little knows about the prevalence and diversity of sand fly bacteria. The main objective of this study was to determine the presence of bacteria of phlebotominae sand flies collected in Hamadan, west of Iran. This information is important in order to development of vector control strategies. The microbial flora of Phlebotomus papatasi and P. sergenti the main vector of Cutaneous Leishmaniasis in the old world, were investigated. We characterized 8 bacteria, including 5 Gram-negative bacteria: Acinetobacter lwoffii, Pseudomonas aeruginosa, Enterobacter cloacae, Edvardsiela sp. and Proteus mirabilis and Gram-positive bacteria: Bacillus subtilis, Staphylococcus saprophyticus and Micrococcus luteus. Our study provides some data on the microbiota diversity of field-collected sand flies for the first time in Hamadan. Our results indicate that there is a range of variation of aerobic bacteria inhabiting sand fly, which possibly reflect the ecological condition of the habitat where the fly breeds. Microbiota is increasingly regarded as an important factor for modulating vector competence in insect vectors. So, mirobiota can be effects on the biology of phlebotominae and their roles in the sandfly-Leishmania interaction. Further experiments are required to clearly delineate the vectorial role of sand flies. Because it is probable that in the future, factors such as environmental changes, migration and urbanization can ease the transmission of leishmaniasis in this area.